Etiology and Outcome of Hepatic Encephalopathy in Bangladeshi Children - Nahar, Luthfun; Mondal, Mohuya; Nahar, Kamrun; Munmun, Sayma Rahman; Marjan, Parisa; Sarker, Mst Naznin; Hasan, ANM Saiful; Pervez, Abu Faisal Md; Karim, ASM Bazlul; Rukunuzzaman, Md (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Hepatic encephalopathy is one of the complications of liver failure which causes increase mortality and morbidity in children. This cross sectional type of observation study was conducted in the department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University of Bangladesh to determine the etiology and outcome of hepatic encephalopathy in Bangladeshi children. Patients between 1 to 18 years were included who fulfilled the West Heaven clinical criteria of hepatic encephalopathy. The data were collected and recorded questionnaire after IRB approval and was analyzed accordingly. Total 32 patients were included in this study; among which 20 were males and 12 were female with a mean age was 8.1±3.5 years. The most common etiologies were Wilson disease (47%), followed by cryptogenic (25%) and Hepatitis A virus (18.8%). Total 9 patients out of 32 were expired, another 8 got discharge with advice, 1 patient recovered after liver transplantation and others were improved with advice of follow up. All the patients were expired who developed hepatic encephalopathy due to Hepatitis A virus except one patient who received liver transplantation from abroad. This study highlights that hepatic encephalopathy from infective diseases as hepatitis A virus leads higher mortality rate in children. Though liver transplantation facility is not available in the developing countries, maintenance of hygiene and vaccination is the main preventive measures to reduce the mortality in children. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):88-91.